Sikap Peduli Lingkungan Siswa Kelas IV SD Negeri IV Sempu - Febiyana, Alva; Erviana, Lina; Nurhayati, Nurhayati (Scholarly Journal of Elementary School, 2024)
This  study  aims  to  analyze:  1)  the  attitude  of  caring  for  the  environment  in  of students;  2)  supporting  factors  caring  for  the  environment  of students.  This  research  is  a  qualitative  research  with  a  descriptive  approach.  The  collecation  of  data  used  in  this  study  is  a  data  collaction  technique  of  observation,  interviews  and  documentation.  The  research  subjects  were  four  grade  students and third .  The  collation  techniques  used  were  observation, interviews and documentation. Data  analysis  technique  using  data collection, techniques, data reducation, data presentation, validation and conclusions.  The  results  of  data  analysis  concluded  that:  1)  the  attitude  of  caring  for  the  environment  in  grade  IV  students  at  SD  Negeri  4  Sempu  showed  very  good  results, the thing that  needs to be improved is the  proessing  of  waste  into  useful and creative  goods.  2) The  supporting  factors  for caring  for  the  environment  in  class  IV  SD  Negeri  4  Sempu  students  are self  motivation,  parental  motivation, and  teachers.  Then  the  inhibiting  factor  is  the  frend  factor  around.